Management of Red Palm Weevil, Rhynchophorus ferrugineus (Olivier): Emerging Trends and Challenges - Faleiro, Jose Romeno; A F El-Shafie, Hamadttu (Indian Journal of Plant Protection, 2025)
The Red Palm Weevil (RPW) Rhynchophorus ferrugineus (Olivier) has emerged as a key pest of palms in diverse agro-ecosystems worldwide. During the mid-1980s RPW gained foot hold on date palm in the Middle East and has since spread rapidly throughout the world. Recent reports suggest that it has invaded the Black Sea basin countries, East Africa, South Eastern Europe and South America. Although palms detected in the early stage of attack respond to curative chemical treatment, the cryptic nature of the pest makes detection of infested palms difficult. The Food and Agriculture Organization of the UN through the ‘Rome Declaration’ of 2017 calls for the urgent need to combat RPW by collaborative efforts and commitments at the country, regional and global levels to stop the spread of this devastating pest. There exist several drawbacks and challenges in each component of the current IPM strategy, including the non-availability of an efficient, easy to use and cost effective infestation detection device, labour intensive protocol for the maintenance and servicing of food baited pheromone traps, over dependence of chemical treatments, laborious and costly removal and disposal of severely infested palms, lack of effective biological control agents in the field, poor farmer participation in the control programmes, together with inefficient data collection and reporting for proper monitoring and validation of area-wide RPW-IPM programs. Furthermore, weak enforcement of pre and post entry quarantine regulations is also a major impediment in controlling and stopping the spread of RPW. This presentation outlines the emerging trends and challenges facing the efficient management of this dreaded pest of palms.